Realization of Boolean Logic Functionality Using Redox‐Based Memristive Devices. (18th June 2015) - Siemon, Anne; Breuer, Thomas; Aslam, Nabeel; Ferch, Sebastian; Kim, Wonjoo; van den Hurk, Jan; Rana, Vikas; Hoffmann‐Eifert, Susanne; Waser, Rainer; Menzel, Stephan; Linn, Eike
Abstract : Emerging resistively switching devices are thought to enable ultradense passive nanocrossbar arrays for use as random access memories (ReRAM) by the end of the decade, both for embedded and mass storage applications. Moreover, ReRAMs offer inherent logic‐in‐memory (LIM) capabilities due to the nonvolatility of the devices and therefore great potential to reduce the communication between memory and calculation unit by alleviating the so‐called von Neumann bottleneck. A single bipolar resistive switching device is capable of performing 14 of 16 two input logic functions in the logic concept presented by Linn et al. ("CRS‐logic"). In this paper, five types of selectorless devices are considered to validate this CRS‐logic concept is experimentally by means of the IMP and AND logic operations. As reference device a TaO x ‐based ReRAM cell is considered, which is compared to three more advanced device configurations consisting either of a threshold supported resistive switch (TS‐ReRAM), a complementary switching device (CS), or a complementary resistive switch (CRS). It is shown that all of these devices offer the desired LIM behavior. Moreover, the feasibility of XOR and XNOR operations using a modified logic concept is applied for both CS and CRS devices and the pros and cons are discussed. Abstract : Resistive switching devices enable sequential logic‐in‐memory operations. The feasibility of 14 of 16 two input Boolean logic functions is proven experimentally for: redox‐based resistive switching cells (ReRAMs), ReRAMs offering inherent threshold switching, ReRAMs offering complementary switching (CS), and complementary resistive switching (CRS) cells. Moreover, it is shown that CS and CRS cells also enable the two remaining functions, XOR and XNOR.